A Comparative Assessment of Modern Cyclization Methods of Substituted Alkynyl Esters, Ethers, and Acids - Soltani, Yashar; Wilkins, Lewis C.; Melen, Rebecca L. (Synlett, 2018)
Naturally occurring heterocycles such as pyrones, dihydropyrones, and isocoumarins have proven to be highly active biological agents with a vast plethora of applications. Therefore, their synthesis has attracted mentionable notice in recent decades. Of particular synthetic use is the cyclization of substituted alkynyl esters. More recently, main group compounds have been studied to affect this synthetic pathway giving access to a large family of heterocyclic derivatives.
Keywords: 2-pyrone; isocoumarin; dihydropyrone; tris(pentafluorophenyl)borane; electrophiles; tandem; dual catalysis; cyclization